Design and Synthesis of Crown Ether Functionalized Imidazoles as a New type of Building Blocks - Sheng-Hui Li; Jing Xia (E-Journal of Chemistry)
A simple, convenient and efficient synthesis for a series of crown ether functionalized imidazoles from benzo-15-crown-5 (B15C5), benzo-18-crown-6 (B18C6), imidazole (Im), 2-methylimidazole (mIm), benzimidazole (bIm) and 2-methyl benzimidazole (mbIm) is reported. All these compounds obtained were characterized by IR, 1H NMR, ESI-MS and elemental analysis.